Service life extension of reinforced concrete structures using hydrophobic impregnation - Sohawon, Haris (Department of Civil Engineering, 2019)
Over the last few decades, the increasing premature deterioration of reinforced concrete structures, mainly due to rebar corrosion, has become a worldwide concern. This has been attributed to insufficient quality and quantity of cover concrete resulting from inadequate mix design and poor onsite workmanship respectively. Engineers also often lack understanding of concrete durability and prescribe insufficient cover depths relative to the exposure conditions. Concrete degradation has many financial and social implications on a larger scale. Direct costs relate to the repair and rehabilitation of existing structures to maintain serviceability while indirect costs include loss in productivity and reduced economic growth. With increasing demand for infrastructure and subsequent expansion of the built environment, there is greater need for concrete to withstand and perform in corrosive environments. Hence, designing for durability has gained significant importance amongst engineers and other stakeholders in the construction industry. Furthermore, the appearance of cracks can be considered as an inevitable phenomenon in the design life of reinforced concrete structures, due to concrete being an inherently cracked material. The presence of cracks within the cover zone changes the dynamics of transport mechanisms and corrosion development. Cracks provide preferential ingress paths for deleterious species such as chlorides and this leads to a reduction in the time taken for reinforcement corrosion initiation and thus reduces the service life of the structure. Most service life models also consider concrete only in the uncracked state, leading to an overestimation of the actual performance and design life of reinforced concrete infrastructure. Extensive research has been carried out to find means to promote the service life of reinforced concrete structures in aggressive environments. Hydrophobic (silane) impregnation represents a cost-effective way to increase the durability of concrete structures in cases where insufficient cover quality and depth have been achieved. The hydrophobic impregnation agent lines the internal capillary pore structure and provides a water-repellent surface without affecting the external appearance of the concrete. Thus, the risk of reinforcement corrosion and subsequent deterioration can be reduced as the ingress of water-dissolved aggressive species is minimised or prevented. The influence of silane impregnation on chloride ingress is well documented in literature and several experiments have been carried out over the last decades. However, there is limited work on the service life modelling of silane treated concrete. Hence, the purpose of this study was to investigate and quantify the influence of silane impregnation as a remedial measure for poor quality cover or insufficient cover depth in newly constructed structures and ultimately predict the time to corrosion initiation for specific cover depths and concrete types. The effectiveness of silane impregnation in cracked concrete was also studied. Two w/b ratios (w/b = 0.45 and w/b = 0.60) and four binder types (CEM I 52.5N, Fly-ash (FA), Ground granulated Corex slag (GGCS) and CEM III/B 42.5N) were selected. Hence, a total of 8 main (normal) concrete mixes and 4 poor quality mixes were used. Poor quality concrete was produced by exposing the concrete specimens to relatively high temperature at early age. Cracked concrete was obtained by loading notched reinforced beams until the formation of cracks. Steel spacers were then placed in the notch and the beams were unloaded to create crack widths of 0.2 mm and 0.6 mm (below and above the commonly assumed crack width threshold of 0.4 mm). Silane treatment was performed at a specimen age of 28 days by applying Sikagard®-706 Thixo at a consumption rate of 400 g/m2 . Several experimental tests were performed on untreated and silane treated concrete. Compressive strength and Durability Index (DI) tests were carried out to characterise the concrete mixes. Accelerated carbonation and moisture profiling tests were undertaken to assess the influence of silane impregnation on concrete carbonation and relative humidity. Finally, uncracked and cracked (untreated and treated) concrete mixes were ponded in sodium chloride (NaCl) solution for 80 days, followed by chloride profiling. The data for the uncracked concrete was curve fitted using a solution to Fick’s second law of diffusion. The regression parameters obtained (surface chloride concentration (Cs) and apparent chloride diffusion coefficient (Da)) were then incorporated in a mathematical solution to Fick’s second law to obtain suitable expressions that describe the penetration of chlorides with time for silane treated and untreated concrete mixes. Hence by determining the time taken for chloride concentration at the rebar level to reach the critical threshold (assumed to be 0.4% by mass of binder), the time to corrosion initiation of untreated and silane treated concrete was predicted for particular cover depths. The results indicate that the silane penetration depth is highly dependent on the quality (porosity) and moisture content of the near surface zone as deeper penetration was recorded in the higher w/b ratio and poor-quality concrete mixes. Silane impregnation also reduced the capillary absorption and chloride conductivity for all the mixes. In terms of the bulk diffusion test, chloride ingress in the treated concrete mixes was suppressed and lower chloride surface concentration (Cs) and apparent chloride diffusion coefficient (Da) were recorded. The influence of silane impregnation on carbonation was negligible in the w/b = 0.45 concrete mixes while a slight decrease in carbonation depth was observed in the w/b = 0.60 concrete mixes. The relative humidity of treated concrete (near the surface) initially increased relative to the untreated concrete. However, the difference in relative humidity between silane-treated and untreated concrete is reduced with time. Higher chloride concentrations were measured in the cracked concrete at depths of 50-60 mm compared to the uncracked concrete. Greater chloride ingress was also recorded in the 0.6 mm crack width relative to the 0.2 mm crack width. For a particular crack width, chloride ingress in cracked concrete was influenced by the type of binder; a significant reduction in chloride content was recorded in the cracked slag (GGCS and CEM III/B) concrete mixes relative to the CEM I mix. The results also suggest that silane impregnation reduces chloride ingress in cracked concrete (up to a crack with of 0.6 mm) and consequently minimises the risk of premature reinforcement corrosion initiation, especially in slag concrete. The service life prediction results emphasized the importance of adequate cover depths in the extreme marine exposure class (XS3) and highlighted the superior performance of slag concrete relative to CEM I concrete. A lower rate of chloride ingress was predicted in the silane treated concrete and consequently to achieve the same time to corrosion initiation, smaller cover depths are required. Alternatively, the results also show that the initiation period of rebar corrosion in structures with insufficient cover depth and quality can be effectively extended using silane impregnation.